PENGARUH PERBANDINGAN TALAS KIMPUL (Xanthosoma sagittifolium) DENGAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP KARAKTERISTIK SATE LILIT KELADI - Putri, Putu Lisa Adinda; Yusa, Ni Made; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study aims to determine the effect of xanthosoma and white oyster mushroom on the characteristics  of sate lilit keladi, and to know the right ratio of xanthosoma and white oyster mushroom on the characteristics of sate lilit keladi. The experimental design used was completely randomized design with the treatment ratio of xanthosoma and oyster mushroom, which consists of 6 levels such as: 100% : 0%, 90% : 10%, 80% : 20%, 70% : 30%, 60% : 40%, 50% : 50%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analysed by analysis of variance and if the treatment had an effect on the variable then continued with Duncan test. The result showed xanthosoma and white oyster mushroom ratio had a significant effect on water content, ash content, fat content, protein content, carbohydrate  content, coarse fiber content, hardness, color (hedonic), aroma (hedonic), texture (hedonic and  scoring),  taste  (hedonic  and  scoring)  and  overall  acceptance   (hedonic).   Comparison   of  50% xanthosoma  and 50% white oyster mushroom  had the best characteristics,  with 52,86 % water content, 3,31 % ash content, 6,52% protein content, 24,57%  fat content, 12,74%  carbohydrate  content, 35,88% coarse  fiber content,  0,11 kg/5mm  hardness,  color liked, aroma liked, texture  mushy  and rather liked, typical taste rather keladi and liked and overall acceptance liked.